Transplantation of autologous chondrocytes ex-vivo expanded using Thermoreversible Gelation Polymer in a rabbit model of articular cartilage defect - Arumugam, Sivaraman; Bhupesh Karthik, Balasubramanyan; Chinnuswami, Rajeswar; Mori, Yuichi; Yoshioka, Hiroshi; Senthilkumar, Rajappa; Mathaiyan, Rajmohan; Ramalingam, Karthick; Senthilkumar, Preethy; Abraham, Samuel J.K. (Journal of Orthopaedics, 2017)
Graft failure due to de-differentiation of the chondrocytes during in vitro culture and after transplantation is a major hurdle in Autologous Chondrocyte Implantation (ACI). We, herein, report the transplantation of autologous chondrocytes ex vivo expanded using a Thermo-reversible Gelation Polymer (TGP) in a rabbit model. A full thickness chondral defect was created in one of the knee joints in each of the six rabbits of the study and autologous chondrocytes in vitro expanded using TGP scaffold were transplanted after 10 weeks. H & E staining of the biopsy after 6 months revealed maintenance of articular cartilage phenotype.